A new tool for disinfecting household drinking water for rural residents: protonated mordenite-embedded sheet. (21st February 2022) - Johan, Erni; Fernando, Verónica Américo António; Sadia, Salma; Mitsunobu, Satoshi; Hirai, Soichiro; Matsue, Naoto
Abstract: Many rural residents in developing countries drink water contaminated with feces due to inadequate purification, causing many diarrheal deaths, most of them infants. We have fabricated a protonated (H + -retaining) mordenite-embedded non-woven fabric sheet (H-MES) as a new tool for disinfecting drinking water at home. Proton retention amount was 1.2 mmol per gram of mordenite, 75% of its cation-exchange capacity. The H-MES released protons through cation exchange with cations in aqueous solutions, lowering the pH of the solutions to below 4. This low pH led to disinfecting 100 mL of 100-fold diluted TSB solutions containing an Escherichia coli species (DH5 α ). For example, an initial viable count of around 5, 000 CFU mL −1 decreased to 14 CFU mL −1 after 24 h shaking at 25 °C with added H-MES containing 0.2 g protonated mordenite; 3.8×10 7 CFU mL −1 without the H-MES. Adding a nitric acid solution showed a similar effect, but using chemical reagents at home might lead to unexpected accidents. Adding and removing the H-MES to and from household waterpots by hand is easy. Besides the H-MES, similar sheets embedded with bactericides and bacterial adsorbents could be a simple water-disinfection tool for rural residents. HIGHLIGHTS: Health hazards by pathogen-contaminated water are severe among rural residents. A new type of bactericide, protonated mordenite, was embedded on a fabric sheet (H-MES). H-MES disinfected the water containing an E . coli species. Removal of H-MES from treated water is simple by hand. H-MES could be a simple tool for household water disinfection. Graphical Abstract